Ratification of Political Party Management by The Ministry of Law and Human Rights of The Republic of Indonesia (Analysis of The Authority of The Minister of Law and Human Rights in Legalizing The Management of Political Parties): - Munir, Misbahul; Chandra, Anna Erliyana (JASSP, 2022)
Drama over the leadership of political parties is common in Indonesia. Most recently, the drama hit the body of the Democrat Party (Indonesia: Partai Demokrat). Some cadres of the "mercy" party held an Extraordinary Congress (KLB) in Deli Serdang. From this KLB, General Moeldoko (Presidential Chief of Staff) was elected as Chairman of the Democrat Party for the 2021-2025 period, replacing the definitive Chairman of the previous congress, Agus Harimurti Yudhoyono (AHY). As a result, some AHY supporters were inflamed and considered the Deli Serdang KLB invalid because it violated the Democrat Party's Articles of Association and Bylaws (AD/ART). Previously, similar chaos also occurred within other political parties, such as the United Development Party (PPP) and Functional Group Party (Golkar) in 2014-2015. This article uses a juridical-normative research form to dissect several substances relevant to the main topic. The approach used in this research is the case approach. This study finds several problems regarding the ratification of political party management by the Ministry of Law and Human Rights (Kemenkumham), including the strong potential for the Kemenkumham to intervene in the ratification of political party management, as well as their imprudence or lack of caution in various administrative decisions, causing legal uncertainty. The results of this research are to provide additional information to the public regarding the problems and dynamics of authorizing the management of political parties in Indonesia, as well as being a command and control for the Kemenkumham to carry out several its authorities that authorize the management of political parties to be held more professionally and carefully.